Influence of vertical dimension on the degree of dentoalveolar compensation in patients with severe Class III malocclusion - Buczko, Piotr; Szarmach, Iga; Grycz, Monika; Szarmach, Izabela (Journal of Stomatology, 2015)
Introduction. The range of dentoalveolar compensation accompanying severe Class III malocclusions should be taken into consideration when planning orthodontic- surgical treatment. Aim of the study. To evaluate the effect of bones bases inclination on dentoalveolar compensation in patients with severe Class III malocclusions, in whom treatment plan includes SAMRE or TPD therapy. Material and methods. Cephalometric images in the lateral projection and 42 models with skeletal Class III. The material was divided into three groups based on the bones bases angle NLML, accepting the following criteria: less than 20.5° – group of low angle (L), in the range of 20.5°-26.5° – group of average angle (A), more than 26.5° – group of high angle (H). Measurements were made on models using an electronic caliper accurate to 0.01 mm using WALA and FA points for both dental arches (6±6, 5±5, 4±4, 3±3). In estimation of the compatibility of distribution the Shapiro-Wilk test was used. Nonparametric methods were used in statistical conclusions. The evaluation of the differences in the distribution of the quantitative variables between the three groups (L, A, H) was performed using the Kruskal-Wallis test. Post hoc Dwass-Steele- Critchlow-Fligner test and non-parametric Spearman correlation coefficient were used additionally. Results. A statistically significant relationship between the size of the bases angle NLML and widths of the WALA alveolar processes measured at the lower canines region (p=0.042) and upper canines area (p=0.019) was found. A positive correlation between the bases angle and width of the alveolar process in areas: 6+6 (r=0.34, p=0.028), 5 + 5 (r=0.32, p=0.042), and 3+3 (r=0.45, p=0.003) was obtained. The widths of dental arches in the teeth 3-3 and 3+3 regions correlated with the vertical dimension, r=042, p=0.006; r=0.48, p=0.001, respectively. The width between WALA and FA points at 4-4 teeth area correlated negatively with NLML angle (r= -0.32, p=0.039). The evaluation of severity of dental Class III malocclusion by Angle on the right side (KL IIIP) and the left side (KL IIIL) showed statistical significance in both measurements. A positive correlation between M angle and the bones bases inclination (r=0.35, p=0.023) was stated. Conclusions. Bones bases angle NLML determines a more important role in alveolar bone transverse dimension compared with the dental arches. The bones bases inclination has an influence on the dentoalveolar compensation.